Computerized Cardiotocography Analysis: Comparison among Several Parental Ethnic Origins - Di Tommaso,Mariarosaria (2016)
ABSTRACT Objective: We speculate that genetic racial disparity exists in fetal life and can be detected by modern computerized cardiotocography (cCTG) . Methods: This is a retrospective study comparing the results of the cCTG of pregnant patients at 37-42 weeks according to the parental ethnicity (black versus white). A cCTG was performed to analyze the variables of fetal heart rate (FHR). The cCTG variables analyzed were: percentage of signal loss; number of contractions; basal FHR; number of accelerations; number of decelerations; length of high variation episodes; short-term variability (STV); total trace duration time; and number of fetal active movements. Non-stress test (NST) parameters in the two groups were compared using the Mann-Whitney test for continuous data, and the Chi-square test for categorical variables. Results: We found a significantly lower number of active fetal movements (p 1/4 0.007) and longer periods of low variation (p 1/4 0.047) in the cCTG of black patients when compared with white patients. Conclusions: In conclusion, identifying the factors responsible for the variance in the objective analysis of CTG results is important to improve the outcomes of patients. Our study lends further evidence as to the importance of ethnicity in clinical cCTG interpretation.